Terracottas in Motion: A Three-Day ZOOM Colloquium - Maya Muratov; Jaimee Uhlenbrock (Les Carnets de l’ACoSt)
A three-day exploration of the theme of terracottas in motion was organized as a ZOOM colloquium by Maya Muratov and Jaimee Uhlenbrock under the auspices of The Association for Coroplastic Studies.